Gambaran Tipe Self-Presentation melalui Konten Foto Instagram pada Mahasiswi - Alifia Raniaputri Hendraswara; Harlin Nikodemus Hutabarat; Yuliana Hanami (Psympathic : Jurnal Ilmiah Psikologi, 2020)
Instagram is one popular social media that is used, especially among college students. Students tend to do self-presentations to give a good impression to others. This study is conducted using qualitative method to obtain description of the type of students’ self-presentation through photo contents uploaded to their Instagram account. The data was collected from the social media of 10 female college students of Faculty of Communication in Padjadjaran University. The results show that the types of self-presentation performed by the participants were ingratiation, supplication, and enhancement. These three types of self-presentation are the types that are often showed through social media. There were three subjects who used all three types of strategies, four subjects used two types (ingratiation and enhancement) and three subjects used one type, ingratiation. From 192 observed photos, 152 were included in the ingratiation type, 4 in the supplication type, and 34 in the enhancement type.